2015
DOI: 10.1111/mbe.12093
|View full text |Cite
|
Sign up to set email alerts
|

Are Spatial‐Numerical Associations a Cornerstone for Arithmetic Learning? The Lack of Genuine Correlations Suggests No

Abstract: The mental number line metaphor describes how numbers are associated with space. These spatial-numerical associations (SNA) are subserved by parietal structures (mainly intraparietal sulcus [IPS] and posterior superior parietal lobule [PSPL]). Generally, it is assumed that this association is a basic cornerstone for arithmetic skills. In this review, we present a taxonomy of SNAs and outline which of them are related to arithmetic skills. Recent research suggests that not all SNAs are related to arithmetic ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 110 publications
3
72
1
Order By: Relevance
“…Several mathematical concepts, including number sense, are constructed based on spatial-numerical mapping (briefly, associating numbers with positions on a line). It was assumed that this association is a basic cornerstone for arithmetic skills, but recently, Cipora et al (2015) concluded that the relationship between spatial-numerical associations and arithmetic skills are rather weak or caused by mediating variables. Nevertheless, interventions based on relationships between space and numbers can be beneficial for arithmetic skills because space is a powerful tool to understand arithmetic concepts.…”
Section: What Does Brain Research Say?mentioning
confidence: 99%
“…Several mathematical concepts, including number sense, are constructed based on spatial-numerical mapping (briefly, associating numbers with positions on a line). It was assumed that this association is a basic cornerstone for arithmetic skills, but recently, Cipora et al (2015) concluded that the relationship between spatial-numerical associations and arithmetic skills are rather weak or caused by mediating variables. Nevertheless, interventions based on relationships between space and numbers can be beneficial for arithmetic skills because space is a powerful tool to understand arithmetic concepts.…”
Section: What Does Brain Research Say?mentioning
confidence: 99%
“…Directional space representation, on the other hand, specifically includes implicit associations between space and cardinality (e.g., numerical comparison tasks). Other directional associations were reported in the original taxonomy (Cipora et al, 2015) but these associations are not yet studied in the populations examined in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestation of the impairment differs among the groups and among the spatial numerical associations tested. In Table 1, the main findings reported in this review are therefore summarized for each group and organized based on an existing spatial-numerical associations taxonomy (Cipora, Patro, & Nuerk, 2015;Patro, Nuerk, Cress, & Haman, 2014). The central distinction of this taxonomy is based on non-directional (extensions) vs. directional associations between numerical and physical space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various SNA operationalizations described in the literature (for reviews and taxonomies see Patro et al, 2014;Cipora, Patro, & Nuerk, 2015), at least three are commonly used in studies with preschool children.…”
Section: Multiple Number-space Associations In Preschool Childrenmentioning
confidence: 99%